Blockchain-Based Copyright Protection System for Digital Content Creators in Rwanda - Baligira, Ahmed Djibril; Ngugi, Jonathan; Sumbiri, Djuma; Habimana, Patrick (Journal of Information and Technology, 2025)
This research paper explores the application of blockchain technology in protecting the copyright of digital content creators in Rwanda. The study examines current challenges faced by creators in registering and enforcing copyrights and proposes a decentralized system using blockchain to provide transparent, tamper-proof, and verifiable copyright records. Using Ethereum smart contracts and decentralized storage, the proposed system ensures content ownership authentication, traceability, and enforcement mechanisms. It highlights the growing creative economy in Rwanda and the need for modern solutions to safeguard intellectual property. Through a combination of technical implementation and stakeholder feedback, the system demonstrates potential to revolutionize digital rights management for Rwandan artists, musicians, writers, and other content creators. The study examines socio-economic implications for Rwanda, emphasizing how such a system could reduce piracy, enhance digital trust, and foster creative entrepreneurship. By aligning blockchain solutions with existing IP law reforms and educational initiatives, this work lays a foundation for digital content protection policies that could be adopted throughout East Africa. It also includes a flow chart illustrating the process, a prototype design, and policy recommendations, with references to support the analysis.